IMPLEMENTASI PENDIDIKAN BUDI PEKERTI PADA SISWA - Sutrisno Sutrisno; Nurhadi Nurhadi; M Mansur (University of Muhammadiyah Malang, 2016)
Character education is an educational process aimed at learners to develop the values, attitudes, and behaviours that emit noble character or noble character. Research with the aim of, (1) To describe the implementation of character education to students at SMPN 5 Malang; (2) To describe the form of school activities in the implementation of character education to students at SMPN 5 Malang; (3) To explain the constraints faced in the implementation ofcharacter education to students at SMPN 5 Malang; (4) To explain a solution that is made to overcome the obstacles to implementation of character education to students at SMPN 5 Malang. This study uses qualitative research techniques. Researchers directly involved in collecting information related to their topic. The collection of data obtained by observation techniques, interviewing techniques, and technical documentation. The informant information that needs to be explored is the principal SMPN5 Malang, Student representatives, IslamicTeachers, PPKn Teachers, and class 7, 8, and 9. Then the data were analyzed by descriptive qualitative. The results showed that the implementation of character education to students in Junior High School 5 Malang to implement school culture that prays together, implement 5S, flag ceremonies and manners of incorporating the materials into every subject. Form of school activities in the field of religion is Imtaq, Khotmil Qur’an, and commemorating religious holidays. Field of self-development and winning personality to hold extracurricular,flag ceremony, student council activities and comply with regulations. And social fields which carry out social service. Constraints on the internal factors that character education lessons were removed, and students are still unstable, external factors are the impact of globalization, parents and children often indulge milieu wrong. The solution is to provide guidance that provide insight, training and supervision, teachers set a good example, providing facilitiessupporting character education and establish good communication between parents and the school. The conclusion that the implementation of character education to students at SMPN 5 Malang to implement and incorporate the material culture of the school moral and character are integrated into each subject. School events that shape the field of religion, self-development field and superior personality, and social areas. The obstacles are internal factors and external factors. And solutions to overcome these obstacles is to provide guidance, teachers give good example, providing character education support facilities and establish excellent communication between parents and the school.